El artista como dictador social o el político como escenógrafo - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2011)
There’s no doubt that the iconographic potential of Nazi policy was an essential aspect of success over a people who quickly build their Führer as the center of your truth andthe support of his narcissistic image, with a high price to pay, of course . The paroxysmal realization of vanguardistic art, the hypnotic use of iconography that included not only the swastikas, but also the helmets of the Wehrmacht, some kind of boots, iron crosses, etc. realize a common handling practices in politics today, where priority is given to the mediatic fact at the expense of program content. Compared with the impact of the terrorist events of September 11, 2001, are two particular ways of analyzing the aesthetic reach of historical episodes that managed to completely break the barriers of the museum and take over the worldof life. Violence and death seem to be key factors in this particular form of avant-garde aesthetic.